Linguostylistic Features of Literary Texts in Uzbek and Spanish Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article defines the linguo-stylistic features of literary texts in both Uzbek and Spanish languages, focusing on the expressive means and stylistic devices that enrich these literary works. Drawing on theories from text linguistics and cognitive approaches, the study examines how authors in both literary traditions use metaphors, similes, personification, hyperbole, and other stylistic tools to convey meaning, evoke emotions, and create aesthetic value. By comparing the role of stylistic features in both traditions, the study provides insight into how these languages communicate complex human experiences through literary expression.